Mallory goes green! - Friedman, Laurie B. (Darby Creek, 2010)
When Mallory is appointed to the Fern Falls Elementary School Environmental Committee, which is deciding on class projects for the upcoming Green Fair, she rapidly succeeds in alienating her classmates, friends, and family by her overzealous efforts to save the planet.